Therapeutic Effect Of Ashwagandha (Withania Somnifera L.) In Liver Dysfunction Of Old Dogs (Applied Biological Research, 2014)
The present study was aimed to assess the hepatoprotective and anti oxidant potential of hydro-alcoholic root extract of ashwagandha (Withania  somnifera) against liver dysfunction in geriatric canine. Geriatric canine  (50) with hepatic dysfunction were divided randomly into 2 equal groups.  The treatment group animals received principal therapy in combination  with hydro-alcoholic root extract of W. somniferous for 28 consecutive days,  while control group received only principal therapy as per the cause of  disease which resulted in hepatic derangement. The herbal treatment of W.  somnifera root extract significantly improved serum ALT, AST, albumin,  cholesterol and protein levels. SOD, GSH, LPO and catalase levels  regained to normal levels in treatment group animals in post-treatment  period as compared to pre-treatment period. The results suggest that crude  hydro-alcoholic root extract of W. somnifera possesses biologically active  principles that are hepatoprotective and anti-oxidant in nature. It provides an opportunity of alternative therapy with medicinal plant for small  animals that are not able to use the allopathic drugs.
Keywords: Ashwagandha; geriatrics; heopatoprotective; oxidative stress; principal therapy